ANALISIS PENILAIAN TINGKAT KESEHATAN BANK BRI DENGAN MENGGUNAKAN METODE RGEC PERIODE 2014 - 2016 - Hendarwati, Atik (PRIMA EKONOMIKA, 2017)
This study aims to determine the health of Bank BRI period 2014-2016 in terms of Risk Profile, Good Corporate Governance, Earnings and Capital (RGEC). Research data in the form of secondary data in the form of RGEC financial ratios. The data of RGEC's financial ratios are: Non Performing Loan (NPL), Loan to Deposit Ratio (LDR), Net Interest Margin (NIM), Capital Adequacy Ratio (CAR), and Return on Assets (ROA). The result of the research concludes that based on RGEC analysis, Bank BRI is in composite-1 (PK-1) or Very Healthy for the period during its research period